Proprioceptive Reweighting and Postural Control are Impaired Among Elite Athletes Following Anterior Cruciate Ligament Reconstruction - Benoit Attalin; Telma Sagnard; Eric Laboute; Nicolas Forestier; Olivier Rémy-Néris; Brice Picot (International Journal of Sports Physical Therapy)
# Background